EFFECT OF AWARENESS, KNOWLEDGE AND ATTITUDE OF TAXPAYERS TAX COMPLIANCE FOR TAXPAYERS IN TAX SERVICE OFFICE BOYOLALI - Wicaksono, Monot; Lestari, Tutik (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
Tax compliance is a major factor affecting tax revenues. To determine the level of compliance of taxpayers in meeting their tax obligations can be seen from the achievement of revenue targets. This research aims to analyzing the influence of taxpayers’ awareness, knowledge of taxation, and taxpayers’ attitude influential on of docility taxpayers in KPP Pratama Boyolali. Convenience sampling was conducted in this research as a method. Data obtained in the form of primary data questionnaire distributed in KPP Pratama Boyolali and data obtained secondary from KPP Pratama Boyolali. Taxpayers taken as sampled was taxpayers who came to KPP Pratama Boyolali who have NPWP good taxpayers people personally and the body was handed SPT in KPP Pratama Boyolali. This research used Multiple Regression analysis tool. The result of research shows that awareness taxpayers influential significantly against of docility taxpayers. The knowledge of the tax is not influential significantly against of docility taxpayers The attitude of the taxpayers significantly influences taxpayer compliance. Keywords: taxpayer awareness, knowledge of taxation, attitude of the taxpayer on tax compliance.